2015
DOI: 10.1038/nn.4028
|View full text |Cite
|
Sign up to set email alerts
|

mGluR5 in the nucleus accumbens is critical for promoting resilience to chronic stress

Abstract: Resilience to aversive events has a central role in determining whether stress leads to the development of depression. mGluR5 has been implicated in the pathophysiology of depression, but the effect of mGluR5 activity on stress resilience remains unexplored. We found that mGluR5(-/-) (also known as Grm5(-/-)) mice displayed more depression-like behaviors (for example, learned helplessness, social withdrawal and anhedonia) than control mice following exposure to various stressful stimuli. Lentiviral 'rescue' of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…Animal models of depression showed reductions in mGluR5 protein and density in various brain regions (14, 15). Similarly, mGluR5 knockout mice exhibited depressive-like behavior (16) and chronic, but not acute, antidepressant treatment increased mGluR5 expression (17), raising the possibility that therapeutic effects might be mediated by mGluR5 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of depression showed reductions in mGluR5 protein and density in various brain regions (14, 15). Similarly, mGluR5 knockout mice exhibited depressive-like behavior (16) and chronic, but not acute, antidepressant treatment increased mGluR5 expression (17), raising the possibility that therapeutic effects might be mediated by mGluR5 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…GRM5 has previously been associated with a range of behavioural and neurological phenotypes such as depression 27 , OCD 28 , epilepsy 29 , smoking 30 , Alzheimer's disease 31,32 , autism 33 and schizophrenia 34 . A recent study found a role for Metabotropic glutamate receptor 5 (mGluR5) in relation to stress-induced depression in mice 35 and GRM5…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the best available option is alloswitch and its analog compounds, which are freely-diffusible allosteric modulators of metabotropic glutamate 5 (mGlu 5 ) receptors 16,28 . These receptors are important modulators of neurotransmission and synaptic plasticity 29 , and are involved in several neurological conditions 30,31,32,33,34,35 . Alloswitch and its analogs are subtype-selective, allosteric ligands with nanomolar activity that can turn on and off endogenous mGlu 5 receptors in vivo.…”
Section: Introductionmentioning
confidence: 99%